2013
DOI: 10.1158/2326-6066.cir-13-0059-t
|View full text |Cite
|
Sign up to set email alerts
|

Combining Oncolytic HSV-1 with Immunogenic Cell Death-Inducing Drug Mitoxantrone Breaks Cancer Immune Tolerance and Improves Therapeutic Efficacy

Abstract: Although antitumor activity of herpes simplex virus 1 (HSV-1) ICP0 null oncolytic vectors has been validated in murine breast cancer models, oncolytic virus treatment alone is insufficient to break immune tolerance. Thus, we investigated enhancing efficacy through combination therapy with the immunogenic cell death-inducing chemotherapeutic drug, mitoxantrone. Despite a lack of enhanced cytotoxicity in vitro, HSV-1 ICP0 null oncolytic virus KM100 with 5 mmol/L mitoxantrone provided significant survival benefit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 46 publications
(54 reference statements)
3
61
0
Order By: Relevance
“…Mitoxantrone, as an anthracendione, is a structurally related DNA-intercalating compound clinically used for treatment of acute myeloid leukemia, non-Hodgkin's lymphoma and several solid tumors including breast and prostate cancer [38]. ICD induction by mitoxantrone in combination with an oncolytic virus was recently demonstrated to overcome immunologic tolerance established toward cancer antigens [39]. Bugaut et al reported about the ICD activity of the glycopeptide bleomycin, commonly employed for the treatment of testis cancer and Hodgkin lymphoma and acting comparable to anthracyclines primarily via ROS-mediated ER stress [40].…”
Section: Icd-inducing Anticancer Drugsmentioning
confidence: 99%
“…Mitoxantrone, as an anthracendione, is a structurally related DNA-intercalating compound clinically used for treatment of acute myeloid leukemia, non-Hodgkin's lymphoma and several solid tumors including breast and prostate cancer [38]. ICD induction by mitoxantrone in combination with an oncolytic virus was recently demonstrated to overcome immunologic tolerance established toward cancer antigens [39]. Bugaut et al reported about the ICD activity of the glycopeptide bleomycin, commonly employed for the treatment of testis cancer and Hodgkin lymphoma and acting comparable to anthracyclines primarily via ROS-mediated ER stress [40].…”
Section: Icd-inducing Anticancer Drugsmentioning
confidence: 99%
“…The values are average of three wells that used pooled splenocytes from five mice. of potent oncolytic viruses, along with the selection of appropriate combination therapies to enhance immunogenicity 34. …”
mentioning
confidence: 99%
“…4 Studies in preclinical murine tumor models showed that the antitumor activity of the prototype HSV-1 ICP0-null OV KM100 depends on whether the tumor model is tolerized. 4,6 Although in vitro tumor cell cytotoxicity mirrors the in vivo therapeutic efficacy of some OVs, 7 we fail to observe a similar correlation with our herpesvirus-based OVs, 5,6,8 despite the requirement for replication of competent vectors. 4 Thus, the complex molecular interactions that dictate permissivity of oncolytic HSVs in cancer cells remain elusive.…”
Section: Introductionmentioning
confidence: 63%
“…3 We have developed and tested the efficacy of HSV-1 deleted for the viral protein ICP0 as oncolytic vectors. [4][5][6] These OVs show modest in vitro oncolysis mainly in cancer cell types with impaired abilities to mount anti-viral responses. 4 Studies in preclinical murine tumor models showed that the antitumor activity of the prototype HSV-1 ICP0-null OV KM100 depends on whether the tumor model is tolerized.…”
Section: Introductionmentioning
confidence: 99%